The Effect of Transformational Leadership Style, Organizational Culture, And Compensation on Employee Performance at PT. Würth Indonesia, Makassar Branch: JEL Classification: M12, M54, J33, L20 - Chaerul Akbar Arham; Nurmadhani Fitri Suyuthi; Wahyu Wahyu (Journal of Management and Administration Provision, 2026)
The purpose of the study is to examine the role of transformational leadership style, organizational culture, and compensation in solving the employee performance at PT Würth Indonesia Makassar branch. A quantitative approach in the process of conducting this research was applied where 40 employees were involved as a sample. The questionnaire is used to collect the data that is subsequently analysed with the assistance of SPSS (Statistical Product and Service Solution) program version 22. It has been found that: (1) Transformational leadership styles significantly influence positively the performance of the employees with t count 2, 086 greater than t table 1,688, and significant at p-value of less than 0.05. (2) It also has a positive substantial impact on the organizational culture and the t count 2,270> t table 1,688 and the p-value is less than 0.05. (3) The positive and significant effect of compensation on employee performance is indicated with t count 3,237 is more than t table 1,688 and p-value less than 0.05. (4) All three variables have a positive and significant contribution to the employee performance, with F count 9,793 > F table 2,866 and p-value < 0.05, and a determination coefficient of 0.449 showing that all three variables make a contribution to the improvement of employee performance by 44.9. Such findings provide an insight to the management whereby; employee performance can be enhanced by developing leadership styles and good organizational culture and application of a fair system of compensation. It is also a recommendation of this research that further research be conducted using mixed methods (mixed methods) in order to have a more holistic picture.